2017
DOI: 10.1177/1356336x17741402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of perceived mattering, role stress, and emotional exhaustion on physical education teacher/coach job satisfaction

Abstract: , M. A. (2019). Exploring the relationships among perceived mattering, role stress, and emotional exhaustion on physical education teacher/coach job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 56 publications
(106 reference statements)
6
39
1
8
Order By: Relevance
“…Mattering was also reported to be the protective factor against depression symptoms and suicide ideation among young adults [22], [23]. The decision to involve mattering as our main predictor in this current study is also confirmed because it has been established that employees with higher levels of mattering tend to have higher job satisfaction, perceive lower job stress, as well as perceive higher work-life balance [4], [24], [25] that will lead to lower turnover intention [26]. Our second choice as the predictor of turnover intention was the organizational commitment.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Mattering was also reported to be the protective factor against depression symptoms and suicide ideation among young adults [22], [23]. The decision to involve mattering as our main predictor in this current study is also confirmed because it has been established that employees with higher levels of mattering tend to have higher job satisfaction, perceive lower job stress, as well as perceive higher work-life balance [4], [24], [25] that will lead to lower turnover intention [26]. Our second choice as the predictor of turnover intention was the organizational commitment.…”
Section: Introductionsupporting
confidence: 74%
“…In the last few decades, organizations have been downsized in order to survive financial turbulences and increase efficiency [1]. Nevertheless, smaller size of organizations might lead to higher workload that causes burnout and dissatisfaction among employees [2], which might put the employees' mental health at risk [3], [4] and ended up in higher turnover intention [5]. Turnover intention among employees signifies more problems nowadays with smaller, highly-efficient organizations, because the workload has been optimally distributed [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even in the “relatively amotivated” group, absolute scores for autonomous motivation were still rather high, and absolute scores for amotivation were still rather low. Given the large amount of literature that warns against the low level of recognition and the low value that PE teachers perceive in terms of their subject [9,34], the “high autonomous motivation” group found in these PE teachers may be interpreted as a piece of hopeful information for their psychological functioning. In any case, before continuing, it should be noted that the terms “relatively”, “high”, and “low” refer to scores that are compared with the scores of other PE teachers in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This scale examines the burnout dimensions of emotional exhaustion, depersonalization, and reduced personal accomplishment. However, because emotional exhaustion is considered the archetype of burnout [22], and in line with other studies on PE teachers [34], only the five items assessing emotional exhaustion were used in the present study. Example items are, “I feel burned out from my work” and “I feel used up at the end of the workday”.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few years, several studies have focused on the understanding of PE teachers’ wellbeing and mental health [ 32 , 33 ] and some of these have demonstrated the existence of factors which explain why PE teachers orient themselves towards one motivational style rather than another. Some of these factors are the beliefs that teachers hold [ 8 , 34 ], the pressures they feel at their job [ 35 , 36 ], the perceived motivation in the students they teach [ 13 , 27 ] or their own personality disposition [ 37 ].…”
Section: Introductionmentioning
confidence: 99%